The aesthetics of virtual wayang performances during the covid-19 pandemic - Sunardi, Sunardi; Rianto, Jaka; Sulastuti, Katarina Indah; Harpawati, Tatik; Asmoro, Purbo; Sugihartono, Ranang Agung (Institut Seni Indonesia Surakarta, 2023)
This paper discusses the aesthetics of virtual wayang performances by puppeteers. The problems studied are: (1) why puppeteers have a new tendency to perform virtual wayang; and (2) the aesthetic style of the virtual wayang performances. Data collection methods by interviews with puppeteers, literature studies about virtual wayang, and observations of wayang virtual performances by puppeteers were analyzed by aesthetic theory. The study results showed that puppeteers used digital platforms to maintain their profession's continuity and economic living conditions. The tendency of virtual wayang to give rise to an aesthetic style of digital puppets is known as aesthetics of taste, with the orientation of wayang performance to meet public tastes. The conclusion results state that the aesthetic style of the virtual wayang performance: (1) the camera as a representation of the audience's eyes; (2) puppeteers are required to be creative, innovative, and productive; (3) the audience has the freedom to determine their tastes; and (4) the importance of collaboration that must be carried out by the puppeteer.